Highly sensitive fiber optic microseismic monitoring system for tunnel rockburst. (15th February 2022) - Li, Shili; Ni, Yong; Wang, Yu; Shi, Jinhui; Zhang, Shichao; Ge, Qiang; Zhang, Gang; Guang, Dong; Wu, Xuqiang; Tang, Chunan; Yu, Benli
Highlights: An intrinsically secure fiber optic MS monitoring system for rockburst is developed. Performance of the optical system is superior to commercialized electrical system. A large number of effective MS signals have been obtained in field tests. Abstract: By capturing the micro-crack signals of rock mass structure, the microseismic (MS) monitoring technology is a good candidate for the forecasting and early warning of dynamic disaster. In this paper, MS sensors based on fiber optic interferometric scheme are studied and fabricated, and authors develop an 8-channel highly sensitive fiber optic MS system based on space division multiplexing technology to monitor the whole process of rock mass from micro-fracture to macro-damage. Field test of the system is carried out in Hanjiang River to Weihe River Water Diversion Project. The results show that it can realize continuously monitored with high accuracy and reliability in the tunnel and obtain the characteristic of temporal-spatio-strong of MS events, which are superior to the commercialized electrical monitoring equipment. This work shows that using fiber optic interference technology to develop accelerometer for MS monitoring system is both advantageous and feasible with the character of intrinsically safe.